2004
DOI: 10.1038/nsmb840
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic DNA methylation alters chromatin structure and elongation efficiency in mammalian cells

Abstract: Transcriptional silencing in mammals is often associated with promoter methylation. However, a considerable number of genomic methylated CpGs exist in transposable elements, which are frequently found in intronic regions. To determine whether intragenic methylation influences transcription efficiency, we used the Cre/loxP-based system, RMCE, to introduce a transgene, methylated exclusively in a region downstream of the promoter, into a specific genomic site. This methylation pattern was maintained in vivo, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
357
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(402 citation statements)
references
References 50 publications
37
357
1
7
Order By: Relevance
“…In addition, inverse and positive correlations were observed between gene body methylation and expression. The cause and effect of DNA methylation within gene bodies is not fully understood; however, mechanisms leading to faulty gene expression have been postulated including the regulation of transcriptional elongation, 33 cell-type specific selection of alternative promoters, 34 modulating alternative RNA splicing, 35 or defining alternative polyadenylation sites. 36 Genes that are regulated by DNA methylation and provide a selective growth advantage to cancer cells have been referred to as epi-driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inverse and positive correlations were observed between gene body methylation and expression. The cause and effect of DNA methylation within gene bodies is not fully understood; however, mechanisms leading to faulty gene expression have been postulated including the regulation of transcriptional elongation, 33 cell-type specific selection of alternative promoters, 34 modulating alternative RNA splicing, 35 or defining alternative polyadenylation sites. 36 Genes that are regulated by DNA methylation and provide a selective growth advantage to cancer cells have been referred to as epi-driver genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be challenging to understand given the complex association of DNA methylation with gene expression. For examples, dense intragenic DNA methylation alters chromatin structure that reduces the efficiency of Polymerase II elongation, 30 the rate of transcriptional elongation regulating alternative splicing 31 ; transcription influenced by DNA methylation via chromatin remodeling 32 ; and methylation of gene bodies lead alternative splicing and disease-causing mutations. 33 In this study, 10% of the DM CpGs were significantly correlated with the gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently Lorincz et al [4] have shown that the efficiency of transcription can be seriously affected by methylation of non regulatory CpGs dispersed in the body of the gene.…”
Section: Cpg Dinucleotides Location and Func-tionmentioning
confidence: 99%